DAMPAK PEMBELAJARAN LURING DI MASA PANDEMI TRHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPS - Zakarias Iwan Kristiono; Amin Mustajab (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRACTGoal of this study is to see whether offline learning by giving assignments has an impact on cognitive learning outcomes in social studies subjects. Quantitative method with one group pretest-posttest design. Seventh grade students of SMP Negeri 01 Entikong are the population of this study. the sample in this study amounted to 34 students. The instrument of this research consisted of a short description of 5 questions consisting of 2 questions c1, 2 questions c2 and 1 question c3. Data normality was tested using the Kolmogorov-Smirnov statistic test. Hypothesis testing was carried out using the Wilcoxon statistical test because the pretest and posttest data were not normally distributed. The results of the Wilcoxon statistical test showed that there was no difference in the average student learning outcomes before and after taking offline learning by giving assignmentsKeywords: Offline Learning, Learning Outcomes, Pandemic Period.